2009
DOI: 10.2106/jbjs.h.01266
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Osteochondral Mosaicplasty for Osteochondritis Dissecans of the Elbow in Teenage Athletes

Abstract: Background: Although autologous osteochondral mosaicplasty is widely used as a procedure for osteochondritis dissecans lesions, the effectiveness of this procedure in elbow lesions remains unclear. Our aim was to clarify the surgical efficacy of mosaicplasty for teenage athletes with advanced lesions of capitellar osteochondritis dissecans. Methods: From 2001 to 2006, nineteen teenage male patients who were competitive athletes and had advanced lesions of capitellar osteochondritis dissecans underwent mosaicpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 28 publications
0
81
0
1
Order By: Relevance
“…4,11,12,17,19,30,31,33,35 In particular, recent mosaicplasty of the knee has been useful in enabling reconstruction of the articular surface through the continuity of the hyaline cartilage and the subchondral bone. 1,7,8,26,34 However, results indicate that despite cartilage implant, it is mainly cancellous bone that causes serious limitations, and because insertion of the lateral wall is surgically difficult in patients with extensive loss, the defective portion may not be completely covered and may result in poor outcomes. 26,34 To date, studies have identified progression to arthritis as an underlying factor of poor outcomes of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,11,12,17,19,30,31,33,35 In particular, recent mosaicplasty of the knee has been useful in enabling reconstruction of the articular surface through the continuity of the hyaline cartilage and the subchondral bone. 1,7,8,26,34 However, results indicate that despite cartilage implant, it is mainly cancellous bone that causes serious limitations, and because insertion of the lateral wall is surgically difficult in patients with extensive loss, the defective portion may not be completely covered and may result in poor outcomes. 26,34 To date, studies have identified progression to arthritis as an underlying factor of poor outcomes of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies have followed this approach, and most patients returned to their former sporting activity without progression of degenerative changes. 1,7,8,34 However, unavoidable donor site problems remain a disadvantage. One report showed no adverse effects at the donor site, whereas another described unfavorable donor site problems after mosaicplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is indicated for patients who fail non-operative treatment and those with unstable lesions [6]. The surgical treatments are variable, including debridement, drilling or micro-fracture, fragment fixation, and osteochondral autograft transplantation [1,[7][8][9][10]. Among them, the debridement with fragment fixation is a time-tested procedure and one of the most widely used methods for surgical treatment of unstable capitellum OCD [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage resurfacing techniques have become a clinical reality and provided for successful treatment of osteochondral defects. 9,19,21,30 Iwasaki et al 15 consider that these techniques can be effectively applied to unstable OCD lesions with displaced or detached fragment(s) and to failed operative cases.…”
Section: Discussionmentioning
confidence: 99%